THE INFLUENCE OF PRODUCT DIVERSITY AND STORE ATMOSPHERE ON CUSTOMER SATISFACTION AT MINISO MANADO - Pojoh, Lourina S.A.; Kindangen, Paulus; Arie, Fitty V. (Universitas Sam Ratulangi, 2019)
Abstract: Diversity of business keeps developing through times, which creates more fierce competition in business. Companies do marketing strategies to survive the competition and to stay relevant with the industry. Companies have many ways to make the business become more competitive and can overcome the competition. One of the things that can be done to survive in the industry is to pursue customer satisfaction. There are many ways to pursue customer satisfaction in which there are a diversity of products and the atmosphere of the store offered. So this research aims to know the influence of product diversity and store atmosphere on customer satisfaction at Miniso Manado. This study uses a quantitative method with questionnaires used to collect the data. This research derived and examined the model through ordinal regression model in a sample of 100 respondents who have already bought a product at Miniso Manado. The finding of this research shows that the product diversity and store atmosphere have no significant influence on customer satisfaction at Miniso Manado. Retailers should pay attention to other things such as price, the quality of product, and the service.Â Keywords: product diversity, store atmosphere, customer satisfaction